Characterization of Newcastle Disease Virus in Southeast Asia and East Asia: Fusion Protein Gene - Arif Nur Muhammad Ansori; Viol Dhea Kharisma (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
The aim of this study was to generate the bioinformatics analysis of the circulating NDVs in Southeast Asia, East Asia, and the vaccine virus strains through a database of isolates stored in GenBank® (National Center for Biotechnology Information, USA). The used isolates were AJ629062.1 (La Sota), AF309418.1 (B1), EF201805.1 (Mukteswar), KT445901.1 (Komarov), JX524203.1 (V4), AY935499.2 (I-2), KC987036.1 (F), KF767104.1 (Indonesia), KF767105.1 (Indonesia), KF767106.1 (Indonesia), HQ697255.1 (Indonesia), HQ697256.1 (Indonesia), HQ697261.1 (Indonesia), JX012096.2 (Malaysia), GU332646.1 (Vietnam), AF358786.1 (Taiwan), AF358788.1 (China), KT380032.1 (Republic of Korea), and KC503416.1 (Japan). As the results, this study have revealed the data of homology, pathotype, genetic distance, B cell epitope prediction, and molecular phylogenetic analysis of circulating NDVs in Southeast Asia and East Asia and vaccine virus strains. Thus, the results of this study can be used as a reference for vaccine design studies in the applications of poultry vaccine industryReceived: 28 August 2019; Accepted: 31 December 2019; Published: 11 January 2020.